Adaptive RF Front-Ends for Hand-held Applications - van Bezooijen, Andre; Mahmoudi, Reza; van Roermund, Arthur H.M (Analog Circuits and Signal Processing,, 2011)
The RF front-end - antenna combination is a vital part of a mobile phone because its performance is very relevant to the link quality between hand-set and cellular network base-stations. The RF front-end performance suffers from changes in operating environment, like hand-effects, that are often unpredictable. Adaptive RF Front-Ends for Hand-Held Applications presents an analysis on the impact of fluctuating environmental parameters. In order to overcome undesired behavior two different adaptive control methods are treated that make RF frond-ends more resilient: adaptive impedance control, and adaptive power control. Several adaptive impedance control techniques are discussed, using a priori knowledge on matching network properties, in order to simplify robust 2-dimensional control. A generic protection concept is presented, based on adaptive power control, which improves the ruggedness of a power amplifier or preserves its linearity under extremes. It comprises over-voltage, over-temperature, and under-voltage protection.